Perceived sociocultural impacts of tourism and community participation: A case study of Langkawi Island - Jaafar, Mastura; Rasoolimanesh, Mostafa S.; Ismail, Safura (SAGE, 2015)
Using partial least squares-structural equation modeling, we investigated the relationship between residents’ perceptions of the sociocultural impacts of tourism development and community participation in Pantai Cenang, Langkawi Island. We also investigated the moderating role of gender, age and education level on these relationships. The results revealed significant positive relationships between the positive and negative perceptions of residents and community participation; moreover, residents’ gender and age had a moderating effect on these relationships. These findings have implications for tourism development planners and government authorities seeking to expand the involvement of local residents in tourism developments.